Variants in TRIM44 Cause Aniridia by Impairing PAX6 Expression. Issue 12 (9th October 2015) - Zhang, Xibo; Qin, Gang; Chen, Guilan; Li, Tao; Gao, Linghan; Huang, Li; Zhang, Ying; Ouyang, Ke; Wang, Yuqi; Pang, Yu; Zeng, Bo; Yu, Ling
Abstract : PAX6 is a transcription factor controlling the development of the eyes. The authors found that TRIM44 is a novel negative regulator for PAX6 expression. The G155R mutation in TRIM44 enhances its activity, causing PAX6 deficiency and aniridia in patients. ABSTRACT: Congenital aniridia is a genetic disorder that manifests as iris hypoplasia and other associated ocular complications. Mutations in the paired box 6 ( PAX6 ) gene are considered the major cause of aniridia. In this study, we identified four mutations exclusively presented in aniridia patients from a four‐generation Chinese pedigree, including two single nucleotide substitutions in the 3′UTR of PAX6 (NM_000280.4:c.[*76G>A; *2977C>A]) and two missense mutations in tripartite motif containing 44 ( TRIM44, NM_017583.4:c.[191C>A; 463G>A]), which lead to amino acid changes p.S64Y and p.G155R, respectively. Bioinformatic analyses revealed that the two 3′UTR mutations of PAX6 disrupted microRNA binding motifs in the wildtype 3′UTR sequence. Luciferase reporter assay and Western blotting with predicted microRNAs showed that the two 3′UTR mutations could only increase or have no effect on the expression of PAX6. Therefore, they would not be the cause of aniridia that resulted from PAX6 deficiency. Instead, we found that overexpression of TRIM44 significantly reduced the expression of PAX6 in human lens epithelial cells, and the p.G155R mutant exhibited much stronger effect than the wildtype form. We conclude that inhibition of PAX6 expression by mutant TRIM44 is a novel pathogenic mechanism for aniridia.